Undisclosed chemicals - implications for risk assessment: A case study from the mining industry - Singh,K; Oates,C; Plant,J; Voulvoulis,N (Environment International, 2014)
Many of the chemicals used in industry can be hazardous to human health and the environment, and some formu-lations can have undisclosed ingredients and hazards, increasing the uncertainty of the risks posed by their use. Theneed for a better understanding of the extent of undisclosedinformation in chemicals arose from collecting data onthe hazards and exposures of chemicals used in typical mining operations (copper, platinum and coal). Four maincategories of undisclosed chemicals were defined (incomplete disclosure; chemicals with unspecific identities; rel-ative quantities of ingredients not stated; and trade secret ingredients) by reviewing material safety data sheet(MSDS) omissions in previous studies. A significant number of chemicals (20% of 957 different chemicals) acrossthe three sites had a range of undisclosed information, with majority of the chemicals (39%) having unspecificiden-tities. The majority of undisclosed information was found in commercially available motor oils followed by cleaningproducts and mechanical maintenance products, as opposed to reagents critical to the main mining processes. Allthree types of chemicals had trade secrets, unspecific chemical identities and incomplete disclosures. These typesof undisclosed information pose a hindrance to a full understanding of the hazards, which is made worse whencombined with additional MSDS omissions such as acute toxicity endpoints (LD50) and/or acute aquatic toxicityendpoints (LC50), as well as inadequate hazard classifications of ingredients. The communication of the hazard in-formation in the MSDSs varied according to the chemical type, the manufacturer and the regulations governing theMSDSs. Undisclosed information can undermine occupational health protection, compromise the safety of workersin industry, hinder risk assessment procedures and cause uncertainty about future health. It comes down to theduty of care that industries have towards their employees. With a wide range of chemicals incr